Spatial distribution and trends of anemia among pregnant women in Ethiopia: EDHS 2005–2016 - Ayele, Molla Abate; Fenta, Haile Mekonnen; Zike, Dereje Tesfaye; Tesfaw, Lijalem Melie (Frontiers in Public Health, 2023)
Background: Anemia is a public health problem affecting both developed and developing nations worldwide with a significant consequence on health and economic growth. The problem is more severe in pregnant women. Hence, the main purpose of this study was to determine the factors of anemia levels among pregnant women in zones in Ethiopia. Methods: We utilized data from the 2005, 2011, and 2016 Ethiopian demographic and health surveys (EDHSs), a population-based cross-sectional study. The study includes 8421 pregnant women. An ordinal logistic regression model with spatial analysis was used to explore factors of anemia levels among pregnant women. Result: About 224(2.7%), 1442 (17.2%), and 1327 (15.8%) pregnant women were mild, moderate, and severely anemic respectively. The lowest value of AIC revealed that the partial proportional odds model best fitted the data. The middle wealth index of 15.9% (OR=0.841, CI: 0.72-0.983) and richest wealth index of 51% (OR=0.49, CI: 0.409-0.586) were less likely anemic compared to the poorest wealth index, age group of mother 30-39 was 42.9% (OR=0.571, CI: 0.359-0.908) times less likely to be moderate and above anemic compared to < 20 years, several household members 4-6 were 51% (OR=1.51, CI: 1.175-1.94 more likely moderate and above anemic compared to 1-3. Conclusion: Over one-third of the pregnant women (34.5%) were mild, moderate, or severe anemic. Wealth index, age group, religion, region, number of household members, source of drinking water, and EDHS were significant factors in anemia levels. The prevalence of anemia among pregnant women varied among Ethiopian administrative zones. North West Tigray, Waghimra, Oromia special woreda, West shewa, and East shewa were a high prevalence of anemia.